112k views
18 votes
Someone Help Please:))

Someone Help Please:))-example-1

1 Answer

8 votes

Answer:

(0,3), (1,4) (2,5) and (3,6)

Explanation:

f(x) = x + 3 is equivalent to y = 1x + 3 (y = mx + b)

b = the y intercept, when x is 0.

So y = 3, which means its (0,3)

To check:

f(x) = x + 3

f(0) = 0 +3

f(0) = 3

(0,3)

Now let's try that for all the values (1,2 and 3)

f(x) = x + 3

f(1) = 1 + 3

f(1) = 4

(1,4)

f(x) = x + 3

f(2) = 2 + 3

f(2) = 5

(2,5)

f(x) = x + 3

f(3) = 3 + 3

f(3) = 6

(3,6)

Hope that helps!

User Headbanger
by
5.3k points